Midterm 1

Problem 1

Rewrite the polynomial \[ 4x^6 + 3x^4y^3z + 2x^5yz^2 + x^4y^2z^2 \] using each of the lex, grlex, and grevlex orders.

Solution

  • lex: \(4 x^{6} + 2 x^{5} y z^{2} + 3 x^{4} y^{3} z + x^{4} y^{2} z^{2}\)
  • grlex: \(2 x^{5} y z^{2} + 3 x^{4} y^{3} z + x^{4} y^{2} z^{2} + 4 x^{6}\)
  • grevlex: \(3 x^{4} y^{3} z + 2 x^{5} y z^{2} + x^{4} y^{2} z^{2} + 4 x^{6}\)

Problem 2

Compute the quotient and remainder of \(4x^4-5x+3\) on division by \(2x^2-x+1\).

Solution

We find a quotient of \(2 x^{2} + x - \frac{1}{2}\) and remainder \(-\frac{13}{2} x + \frac{7}{2}\).

Problem 3

Consider the following polynomials: \[\begin{align*} f_1 &= x^4 + 4x^3 + 5x^2 + 4x + 1\\ f_2 &= 2x^4 + 7x^3 + 4x^2 - 2x - 1\\ f_3 &= x^3 + 6x^2 + 10x + 3 \end{align*}\] Compute \(\gcd(f_1,f_2,f_3)\).

Solution

First we compute the gcd of \(f_1\) and \(f_2\) via the Euclidean algorithm. The remainder of \(f_2\) on division by \(f_1\) is \[ r_1 = -x^3 - 6x^2 - 10x - 3.\] The remainder of \(f_1\) on division by \(r_1\) is \[ r_2 = 7x^2 + 21x + 7.\] Note that \(r_2 = 7(x^2+3x+1)\). The remainder of \(r_1\) on division by \(r_2/7\) is \(0\). Thus \[\gcd(f_1, f_2)=x^2+3x+1.\] Now we compute \(\gcd(f_3,x^2+3x+1)\). The remainder of \(f_3\) on division by \(x^2+3x+1\) is \(0\). Thus \[\gcd(f_1,f_2,f_3) = x^2+3x+1.\]

Problem 4

Consider the following polynomials: \[\begin{aligned}[c] f &= x^4 + x^3 - x^2 + 2x - 6 \end{aligned} \quad\quad\quad\quad \begin{aligned}[c] g_1 &= x^3-3x^2+2x-6\\ g_2 &= x^3-2x^2+2x-4 \end{aligned}\] Determine whether \(f\) is in the ideal \(\langle g_1, g_2 \rangle\).

Solution

First we compute \[\gcd(g_1,g_2)\] via the Euclidean algorithm. The remainder of \(g_1\) on division by \(g_2\) is \(-(x^2+2)\), which divides \(g_2\). Thus \(\gcd(g_1,g_2)=x^2+2\) or, equivalently, \(\langle g_1,g_2 \rangle = \langle x^2+2\rangle\). The remainder of \(f\) on division by \(x^2+2\) is \(0\) so \(f\) is in the ideal.

Problem 5

Consider the following polynomials: \[\begin{aligned}[c] f &= x^3y^2-xy^3+3xy\\ \end{aligned} \quad\quad\quad\quad \begin{aligned}[c] g_1 &= xy^2+2y\\ g_2 &= x^2y-xy\\ g_3 &= 3y^2-4 \end{aligned}\] Compute the remainder of \(f\) on division by the ordered set \(G=(g_1,\ g_2,\ g_3)\) using the division algorithm and the lex order.

Solution

We apply the division algorithm, indicating the state after each iteration through the main loop in the following table:

\(p\) \(q_1\) \(q_2\) \(q_3\) \(r\)
\(x^3y^2-xy^3+3xy\) \(0\) \(0\) \(0\) \(0\)
\(-2x^2y-xy^3+3xy\) \(x^2\) \(0\) \(0\) \(0\)
\(-xy^3+xy\) \(x^2\) \(-2\) \(0\) \(0\)
\(xy+2y\) \(x^2-y\) \(-2\) \(0\) \(0\)
\(2y^2\) \(x^2-y\) \(-2\) \(0\) \(xy\)
\(\frac{8}{3}\) \(x^2-y\) \(-2\) \(\frac{2}{3}\) \(xy\)
\(0\) \(x^2-y\) \(-2\) \(\frac{2}{3}\) \(xy+\frac{8}{3}\)

Thus, the remainder is \(xy+\frac{8}{3}\).

Problem 6

Determine whether the following ideals are equal: \[\begin{align*} I &= \langle x, y^2 \rangle\\ J &= \langle x^3+y^2, 2x+y^2, xy^3-y^3 \rangle \end{align*}\]

Solution

From the equations \[\begin{align*} x^3+y^2 &= (x^2)(x) + (1)(y^2)\\ 2x+y^2 &= (2)(x) + (1)(y^2)\\ xy^3-y^3 &= (y^3)(x)+(-y)(y^2) \end{align*}\] we conclude that \(J \subseteq I\).

For the converse, note that \(x+\frac{1}{2}y^2 \in J\). Thus if \(xf+g \in J\) then \[xf+g-f\left(x+\frac{1}{2}y^2\right)=-\frac{1}{2}y^2f+g \in J.\] Thus \[xy^3-y^3 \in J \implies -\frac{1}{2}y^5-y^3 \in J\] and \[\begin{align*} & x^3+y^2 & \in J\\ \implies -\frac{1}{2}x^2y^2+y^2 & \in J\\ \implies \frac{1}{4}xy^4+y^2 & \in J\\ \implies -\frac{1}{8}y^6+y^2 & \in J. \end{align*}\] We see that \(\gcd(-\frac{1}{2}y^5-y^3,-\frac{1}{8}y^6+y^2)=y^2\) either via the Euclidean algorithm or by inspection since \[\begin{align*} -\frac{1}{2}y^5-y^3 &= \left(-\frac{1}{2}y^2-1\right)y^3\\ -\frac{1}{8}y^6+y^2 &= \left(-\frac{1}{8}y^4+1\right)y^2 \end{align*}\] Thus \(y^2 \in J\). Thus \(2x+y^2-y^2=2x \in J\). We conclude that \(I \subseteq J\).

Thus the two ideals are equal.

Problem 7

Let \(I=\langle f_1, \ldots, f_s \rangle\) be an ideal of \(k[x_1,\ldots, x_n]\). Prove that \(I=k[x_1,\ldots,x_n]\) if and only if there exist polynomials \(h_1, \ldots, h_s \in k[x_1,\ldots,x_n]\) such that \(h_1f_1 + \cdots + h_sf_s = 1\).

Solution

Suppose \(I=k[x_1,\ldots,x_n]\). By definition of generating set, every element of \(I\) can be written in the form \(h_1f_1 + \cdots + h_sf_s\) for some set of polynomials $h_1, , h_s. Since \(I\) contains every polynomial, this is true in particular for \(1\).

For the converse, suppose \[1=h_1f_1 + \cdots + h_sf_s\] for some polynomials \(h_1, \ldots, h_s\). We have \(I \subseteq k[x_1,\ldots, x_n]\) from the definition of ideal. Now suppose \(g \in k[x_1,\ldots,x_n]\). Multiplying both sides of the equation above by \(g\) we obtain \[g=(h_1f_1 + \cdots + h_sf_s)g=(h_1g)f_1 + \ldots (h_sg)f_s.\] Thus \(g\) is a polynomial linear combination of \(f_1,\ldots, f_s\); in other words \(g \in I\). Thus \(k[x_1,\ldots,x_n] \subseteq I\). Thus \(I=k[x_1,\ldots,x_n]\) as desired.

Problem 8

Let \(I,J\) be ideals in \(k[x_1,\ldots,x_n]\). Prove that \(I \cap J\) is also an ideal.

Solution

Recall that \(I\) is an ideal if and only if it satisfies

  • \(0 \in I\).
  • If \(f,g \in I\), then \(f+g \in I\).
  • If \(f \in I\) and \(h \in k[x_1,\ldots,x_n]\), then \(hf \in I\).

Since \(0 \in I\) and \(0 \in J\), we see that \(0 \in I \cap J\).

Suppose \(f,g \in I \cap J\). Then \(f,g \in I\) and so \(f+g \in I\). Similarly, \(f+g \in J\). Thus \(f+g \in I \cap J\).

Suppose \(f \in I \cap J\) and \(h \in k[x_1,\ldots,x_n]\). Then \(f \in I\) and so \(hf \in I\). Similarly, \(hf \in J\). Thus \(hf \in I \cap J\).

Thus \(I \cap J\) is an ideal as desired.